Effect of Hydro-alcoholic Extract of Rosemary in Comparison with Alprazolam on Learning under Stress Conditions in Rats - Mehrdad Modaresi; Masoume Amoorizi (Fasa University of Medical Sciences, 2018)
Background & Objective: Many anti stress drugs have a lot of side effects on learning. The aim of this study was to compare the effect of Rosemary plant and Alprazolam on learning under stress conditions in laboratory mice. Materials & Methods: In this experimental study, 60 adult female rats were used. In order to investigate the learning capacity under stress conditions, the rats were divided into 6 groups of control, stress, alprazolam and the three experimental groups that received the hydro-alcoholic extract of rosemary plants at doses of 50, 100 and 200. In all of the samples (except the control group) 30 minutes after injection, the mice were placed in a dark box for 50 minutes for stress. Subsequently, observational behaviors of the rats were recorded by using mouse maze. The results were analyzed using SPSS software. Results: The results showed that rosemary hydro alcoholic extract at 100 and 200 mg/kg compared to the stress and alprazolam group significantly decreased the time to reach the target box in the Maze form, which indicates a reduction on effect of stress on the learning, while the number of errors in selecting the target box (reaching the target) at a dose of 200 mg/kg shows a significant decrease with the stress and drug group. Conclusion: According to the results, effective compounds in rosemary extract in two doses of 100 and 200 mg/kg can increase the learning in these conditions with the effect of reducing stress.